Catalytic dehydration of glycerol to acrolein over M2.5H0.5PW12O40 (M = Cs, Rb and K) phosphotungstic acids: Effect of substituted alkali metals - Hamid, Sharifah Bee Abd; Daud, N.A.; Suppiah, Durga Devi; Yehya, W.A.; Sudarsanam, P.; Bhargava, S.K. (Elsevier, 2016)
Catalytic conversion of glycerol into value-added chemicals, particularly acrolein via acid-catalyzed dehydration route has received much attention due to the potential uses of acrolein. This work reports the synthesis of various alkaline metal substituted phosphotungstic acid (H3PW12O40, HPW) catalysts, namely M2.5H0.5PW12O40 (M = Cs, Rb and K) using a controlled precipitation method. A systematic structural, morphology, and chemical characterization were conducted using various analytical techniques. XRD studies revealed that the incorporation of alkaline metals in H3PW12O40 leads to decreased crystallite size and enhanced lattice strain. N2 adsorption–desorption studies show that the specific surface area of H3PW12O40 is significantly improved from 5 to 82 (K2.5H0.5PW12O40), 103 (Rb2.5H0.5PW12O40), and 94 m2/g (Cs2.5H0.5PW12O40). XRD, Raman, and FT-IR studies confirm the Keggin structure of all the alkaline metal substituted HPW catalysts. The acidity strengths estimated by NH3-TPD analysis were obtained in the following order: H3PW (2654.91 μmole/g) > K2.5H0.5PW (1060.10 μmole/g) > Rb2.5H0.5PW (762.08 μmole/g) > Cs2.5H0.5.5PW (461.81 μmole/g). Although alkaline metal substituted H3PW12O40 catalysts exhibit higher specific surface area and smaller crystallite size compared to parent H3PW12O40 low glycerol conversions were found for substituted H3PW12O40 catalysts. As well, the parent H3PW12O40 catalyst shows an excellent acrolein selectivity (95%) which is much higher than that of Cs2.5H0.5.5PW (81.9%) and very close to the selectivities obtained over Rb2.5H0.5PW (95.1%) and K2.5H0.5.5PW (95.6%) catalysts. The catalytic performance of H3PW12O40 and M2.5H0.5PW12O40 materials is directly proportional to their acidic strengths, indicating that the catalyst acidity is a key factor for achieving better results in glycerol dehydration.